Pengembangan Potensi Universitas Wijaya Kusuma Surabaya Menjadi Universitas Riset melalui Pembentukan Kelompok Riset – Tinjauan Literatur - Sri Lestari Utami (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2022)
Various universities founded as research universities in the 19th century conducted research that assisted the progress of various fields in European and American countries. Research universities/research-based universities are characterized by the presence of research activities in the Tri Dharma of Higher Education. Several universities in Indonesia have declared themselves to be research universities, and others are in the process of doing so. Research universities must meet various indicators, all of which stem from research activities. The purpose of this paper is to investigate and compare the readiness of Universitas Wijaya Kusuma Surabaya (UWKS) to become a research university. One method for achieving these goals is the formation of research groups. This essay uses a narrative review design. A UWKS is a private university founded in 1981 in Surabaya, East Java. A long track record of research since its establishment is sufficient provision to prepare it to become a research university. This is also supported by the university's academic community and the foundation that manages it, when viewed from the vision, mission, and objectives. The formation of various research groups could be the start of the development of research universities. They will enable lecturers to produce targeted outputs as indicators of research performance, such as research groups for early detection of chronic degenerative diseases based on specific Indonesian polymorphisms. The paper's conclusion was that UWKS has the potential to become a research university based on its track record. The formation of many research groups is one way to accomplish this.